Stock market liberalization and operating performance at the firm level - Mitton, Todd (Journal of Financial Economics, 2006)
I use firm-specific measures of openness to foreign investors to study the impact of stock market liberalization on firm-level operating performance. In a sample of over 1,100 firms from 28 countries, firms with stocks that are open to foreign investors experience higher growth, greater investment, greater profitability, greater efficiency, and lower leverage. Strategies to address potential endogeneity suggest that the observed relation reflects, at least in part, a causal effect of openness on operating performance.